Comparison of depression between primary and secondary infertile couples - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2020)
Objective We aimed to compare the depression levels between primary and secondary infertile couples and to investigate the related factors that may affect depression. Study design Two hundred and fifty primary and secondary infertile couples, who admitted to Gynecology and Infertility Clinics of Pendik Teaching and Research Hospital affiliated with Marmara University were enrolled in this study. Sixty-four BMI-matched fertile female patients who applied to the General Gynecology Clinic and their husbands were taken as the control group. Beck Depression Inventory (BDI) form was filled by the infertile couples to evaluate the depression status before they started their cycles. Results The mean total BDI scores were alike between groups among women. Mild depression was found to be higher in the primary infertile women and moderate depression was higher in women of the control group. Women had statistically higher depression scores than male partners. Primary infertile, secondary infertile, and fertile women had higher depression scores than their male partners in the corresponding groups. There was no significant difference in mean total BDI scores among males between the groups. The percentage of distribution of male partners in each level of depression was similar between the groups. Conclusions Only a weak positive correlation between the mean total BDI score and the number of previous treatment cycles was found. Psychiatric support before and during the upcoming fertility treatment might reduce the perception of the probable treatment failure.
Keywords: Infertility; depression; Beck's Depression Inventory; EMOTIONAL DISTRESS; WOMEN; PREVALENCE; ANXIETY; IMPACT; RISK